2016
DOI: 10.1002/jmrs.153
|View full text |Cite|
|
Sign up to set email alerts
|

Early MRI versus conventional management in the detection of occult scaphoid fractures: what does it really cost? A rural pilot study

Abstract: IntroductionTo compare the cost‐effectiveness and patient impact between acute magnetic resonance imaging (MRI) management and conventional management in the diagnosis of occult scaphoid fractures in a rural setting.MethodsConsecutive patients presenting to a rural emergency department (ED) with a suspected scaphoid fracture were randomly assigned to either conventional management (6) or acute MRI management (10) (3 patients were excluded from the study analysis). All healthcare costs were compared between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…However, the true cost to the patient and the healthcare system likely outweighs these small differences in imaging cost. Despite an X‐ray being cheaper than a CT or MRI, multiple studies have found that there is either no significant difference in cost or that serial radiographic surveillance is less cost effective than CT or MRI, and that MRI is overall more cost‐effective than CT due to its higher sensitivity . Patient productivity is a major issue with prolonged unnecessary immobilisation of clinically suspected scaphoid fractures, since immobilising scaphoid casts make working difficult, forcing patients to take leave from work and lose wages.…”
Section: Discussionmentioning
confidence: 99%
“…However, the true cost to the patient and the healthcare system likely outweighs these small differences in imaging cost. Despite an X‐ray being cheaper than a CT or MRI, multiple studies have found that there is either no significant difference in cost or that serial radiographic surveillance is less cost effective than CT or MRI, and that MRI is overall more cost‐effective than CT due to its higher sensitivity . Patient productivity is a major issue with prolonged unnecessary immobilisation of clinically suspected scaphoid fractures, since immobilising scaphoid casts make working difficult, forcing patients to take leave from work and lose wages.…”
Section: Discussionmentioning
confidence: 99%
“…This review identified recent and consistent evidence to support the early use of MRI for suspected scaphoid fractures, as earlier confirmation of diagnosis contributes to reduced immobilisation time, healthcare utilisation and costs . An Australian pilot study in a regional ED setting supported these results, indicating that MRI within 1–3 days following the ED presentation dramatically reduced unnecessary immobilisation and time off work, time of treatment and healthcare usage in their setting, with better patient pain and satisfaction scores than controls . The early use of MRI for suspected scaphoid fractures is further supported in the Western Australian diagnostic imaging pathway .…”
Section: Discussionmentioning
confidence: 79%
“…15,34,55,58,59,61 An Australian pilot study in a regional ED setting supported these results, indicating that MRI within 1-3 days following the ED presentation dramatically reduced unnecessary immobilisation and time off work, time of treatment and healthcare usage in their setting, with better patient pain and satisfaction scores than controls. 69 The early use of MRI for suspected scaphoid fractures is further supported in the Western Australian diagnostic imaging pathway. 70 Anecdotally, the referral of patients with a high clinical suspicion of scaphoid fracture for early MRI is often undertaken at follow up rather than in the ED and may represent an area for practice change.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid protocols in musculoskeletal (MSK) MRI have been used to rule out occult fractures of the hip and wrist in the emergency setting. [27][28][29] When negative, MRI can exclude a fracture with rapidity and certainty, avoiding further testing. When positive, MR can lead to rapid treatment, avoiding complications.…”
Section: Musculoskeletalmentioning
confidence: 99%